Feasibility and short‐term outcome of adjuvant FOLFOX after resection of colorectal liver metastases. Issue 3 (March 2013) - Sakamoto, Yasuo; Beppu, Toru; Miyamoto, Yuji; Okabe, Hirohisa; Ida, Satoshi; Imai, Katsunori; Chikamoto, Akira; Watanabe, Masayuki; Takamori, Hiroshi; Baba, Hideo
Abstract Background The role of adjuvant chemotherapy for stage IV colorectal cancer has so far been under‐investigated. The aim of this study was to assess the feasibility and short‐term outcome of adjuvant chemotherapy with the FOLFOX regimen following liver resection for patients with colorectal liver metastasis (CRLM). Methods From May 2005 to September 2010, 86 patients with CRLM underwent hepatic resection in the Department of Gastroenterological Surgery, Graduate School of Medical Sciences, Kumamoto University. Of these patients, 24 received FOLFOX4 or modified FOLFOX6 as postoperative adjuvant chemotherapy. Results Nineteen male and 5 female patients received adjuvant chemotherapy following liver resection. Twenty‐one (87.5 %) of these patients completed 6 cycles of adjuvant chemotherapy. Five patients required a dose reduction due to neutropenia, and the dose intensities of oxaliplatin and 5‐FU were 93.6 and 94.1 %, respectively. There were no severe adverse events from the treatments. The median follow‐up period was 48.4 months. Recurrences developed in 12 patients, and 3 patients died during the follow‐up period. The 3‐ and 5‐year disease‐free survival and overall survival were 51.6 and 45.1 % and 95.5 and 76.0 %, respectively. Conclusions Adjuvant FOLFOX is feasible and might provide a good prognosis for CRLM patients who undergo liver resection.